Physical exercise is effective for neuropsychiatric symptoms in Alzheimer's disease: a systematic review - Mendonça, Dayanne Christine Borges; Fernandes, Denise Rodrigues; Hernandez, Salma Soleman; Soares, Fernando Diákson Gontijo; Figueiredo, Karina de; Coelho, Flávia Gomes de Melo (Arquivos de Neuro-Psiquiatria, 2021)
Background: Neuropsychiatric symptoms are disorders frequently seen in Alzheimer's disease. These symptoms contribute to reduction of brain reserve capacity and, in addition, they present unfavorable implications, such as: poor prognosis for the disease, increased functional decline, increased burden on the caregiver and institutionalization. This scenario makes neuropsychiatric symptoms one of the biggest problems in Alzheimer's disease, and gives rise to a need for treatments focused on improving these symptoms. Sow progress in drug trials has led to interest in exploring non-pharmacological measures for improving the neuropsychiatric symptoms of Alzheimer's disease, such as physical exercise. Objective: To ascertain the effect of exercise on the neuropsychiatric symptoms of Alzheimer's disease and its implications. Methods: This was a systematic review of effective longitudinal research, conducted by searching for articles in the PubMed, Web of Science, CINAHL and Scopus electronic databases, from 2009 to 2019. Studies in which the sample consisted of elderly people aged 65 years old or over with a diagnosis of Alzheimer's disease were included. Initially 334 articles were identified. After exclusions, 21 articles remained to be read in full. From these, five articles fitted the eligibility criteria, and a further two articles were added through manual searches in the references of the articles found. Results: Out of the seven articles analyzed in this review, five studies revealed that physical exercise had a positive effect on the neuropsychiatric symptoms of Alzheimer's disease. Conclusion: This systematic review indicated that physical exercise is a favorable non-pharmacological means for attenuating the neuropsychiatric symptoms of elderly people with Alzheimer's disease, with special attention to aerobic exercises.
Keywords: Exercise; Alzheimer Disease; Behavioral Symptoms